Comparison of the effect of allopurinol and febuxostat on urinary 2,8-dihydroxyadenine excretion in patients with APRT deficiency: a clinical trial - Edvardsson, Vidar O (Eur J Intern Med, 2017)
INTRODUCTION: Adenine phosphoribosyltransferase deficiency (APRTd) is a rare, but significant, cause of kidney stones and progressive chronic kidney disease. The optimal treatment has not been established. The purpose of this pilot study was to compare the effect of the xanthine oxidoreductase inhibitors allopurinol and febuxostat on urinary 2,8-dihydroxyadenine (DHA) excretion in APRTd patients. MATERIALS AND METHODS: Patients listed in the APRTd Registry of the Rare Kidney Stone Consortium, currently receiving allopurinol therapy were invited to participate. The trial endpoint was the 24-hour urinary DHA excretion following treatment with allopurinol (400 mg/day) and febuxostat (80 mg/day). Urinary DHA was measured using a novel ultra-performance liquid chromatography - electrospray tandem mass spectrometry method. RESULTS: Eight of the 10 patients invited completed the study. The median (range) 24-hour urinary DHA excretion was 116 (75–289) mg at baseline, and 45 (13–112) mg after 14 days of allopurinol therapy (P=0.036). At the end of the febuxostat treatment period, 4 patients had urinary DHA below detectable limits (<20 ng/mL) compared with none of the participants following allopurinol treatment (P=0.036). The other 4 participants had a median urinary DHA excretion of 13.2 (10.0–13.4) mg at the completion of febuxostat therapy (P=0.036). CONCLUSION: Urinary DHA excretion in APRTd patients decreased with conventional doses of both allopurinol and febuxostat. Febuxostat was, however, significantly more efficacious than allopurinol in reducing DHA excretion in the prescribed doses. This finding, which may translate into improved outcomes of patients with APRTd, should be confirmed in a larger sample.